PERCEPTION OF A GROUP OF ELDERLY BY NASF ABOUT THE BENEFITS OF PHYSICAL ACTIVITY FOR HEALTH. (Fiep Bulletin - online, 2018)
The population of elderly people is increasing every day in Brazil and in the world, in many countries this populationhas exceeded 7% of the total population, sparking the search for new studies focused on the needs of this group of individuals.This study aims to: analyze the perception of a group of elderly about the benefits of physical activity for health. This is adescriptive and exploratory character, with PN approach. The results show that the physical activity at work, note that thesedentary stood out among the 15 participants (75%) of the sample, 1 (5%) very active, 2 (10%), 2 (10%) irregularly active b. howmuch physical activity as a means of transportation, it was observed that 7 (25%) are characterized as very active, 9 (45%), 1(5%), and 3 active irregularly (15%) irregularly Active B. With regard to physical activity at home, it was observed that 3 (15%) veryactive, 16 (80%) active and only 1 (5%) sedentary. On physical activities of recreation, 7 (35%) very active, 7 (35%), 1 (5%) active,and irregularly 5 (25%) irregularly active B. Regarding domains obtained through the WHOQOL-Bref, we have good datamedium in all domains, note that the physical domain 84.3% 85.6% psychological, social relations 89.2%, 63.2% environmental,on the quality of life 82.1%. The higher the percentage (closer to 100%) better quality of life. It was observed in this study that thestudied population presents important data regarding the practice of physical activity, especially with regard to good quality of life.Therefore, the physical educator acts as intermediary, taking sports to the community, providing the practitioner wellness, biopsychological and social, it is necessary to conduct new studies to reach a larger audience, and that your data can guide physicaleducation professionals in order to promote a better quality of life among the elderly population.